USE OF COFFEE GROUND WASTE WITH RUBBER WOOD SAWDUST FOR GOLDEN OYSTER MUSHROOM (PLEUROTUS CITRINOPILEATUS SINGER) CULTIVATION MATERIAL - Kamsan, Tanyarat; Kiddee, Peeranart; Wonglom, Prisana (PSRU Journal of Science and Technology, 2021)
The study of using coffee ground waste with rubber wood sawdust for golden oyster mushroom (Pleurotus citrinopileatus Singer) cultivation material was examined. The objectives of this research were to study the growth of gold oyster mushroom and to investigate biological efficiency (% B.E.) and protein of golden oyster mushroom. The experimental design of this research was a completely randomized design (CRD) with 6 treatments and 3 replicates per treatment. The experimental replacement of coffee ground waste with rubber wood sawdust ratios were 20%, 40%, 60%, 80% and 100% and using sawdust only as a control (0% replacement). The results found that the replacement of coffee ground waste with rubber wood sawdust ratio of 20% were the highest number of mushroom (60.42+0.46 unit) and 40% had the most width and wet weight of mushrooms as 5.14+0.02 cm. and 36.28+0.42 g, respectively at the statistically significant level of p<0.05. The comparison of % B.E. with the control found that the replacement of rubber wood sawdust ratio of 40% was the highest 42.68% at the statistically significant level of p<0.05. The results of protein of golden oyster mushroom which the replacement of rubber wood sawdust ratio of 60% and 40% were height 37.15+0.11 and 36.67+0.14 g/100 g at the statistically significant level of p<0.05. Thus, it can be concluded that coffee ground waste can instead of rubber wood sawdust for golden oyster mushroom cultivation.